2018
DOI: 10.1093/molehr/gay019
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-214 from endometrial stromal cells inhibits endometriosis fibrosis

Abstract: This work was supported by grants from the National Natural Science Foundation of China (Grant no. 81771549 Jinwei Miao). The authors declare that there is no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 30 publications
1
59
0
1
Order By: Relevance
“…miR-214, in turn, restrains TLR signaling in this model by directly inhibiting Myd88, an essential TLR adapter protein that mediates downstream NF-ĸB signaling. Consistent with beneficial effects of miR-214 that we observed in ADPKD models, several studies have also reported tumor-suppressive effects of miR-214 in various cancers (21,44).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…miR-214, in turn, restrains TLR signaling in this model by directly inhibiting Myd88, an essential TLR adapter protein that mediates downstream NF-ĸB signaling. Consistent with beneficial effects of miR-214 that we observed in ADPKD models, several studies have also reported tumor-suppressive effects of miR-214 in various cancers (21,44).…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of these data sets revealed that both miR-214 and its host lncRNA Dnm3os are upregulated in multiple PKD models. miR-214 has been linked to inflammation signaling pathways and is found in cells in the tumor microenvironment (20)(21)(22)(23). These observations prompted us to examine the role of miR-214 in ADPKD more closely.…”
Section: Introductionmentioning
confidence: 99%
“…TFMPs participate in thrombus formation and clot propagation (Nomura and Shimizu, 2015). Moreover, following Alleviate PCOS by targeting PDCD4 to promote proliferation and inhibit apoptosis of cumulus cells New therapeutic strategy Zhao et al, 2019 Biomarkers for predicting PCOS Carvalho et al, 2017b Endometriosis Reflect the state of the inflammation and/or procoagulant system Munros et al, 2017 Increase total weight and impair macrophages' phagocytic ability Sun et al, 2019 Contribute to endometriosis by affecting inflammation, angiogenesis, and proliferation in the microenvironment of endometriotic lesions Khalaj et al, 2019 Prediction of successful embryo implantation Parks et al, 2018 Decrease of endometriosis fibrosis by reducing Collagen αI and CTGF mRNA expression Wu et al, 2018 Promote the occurrence of endometriosis and regulate angiogenesis Harp et al, 2016, Qiu et al, 2019 A non-invasive detection marker in the diagnosis of endometriosis Muth et al, 2015 EVs: Extracellular vesicles. PCOS: Polycystic ovary syndrome.…”
Section: Extracellular Vesicles and Polycystic Ovary Syndromementioning
confidence: 99%
“…On the other hand, in terms of pathology, the main feature of endometriosis is ectopic tissue fibrosis, which is characterized by excessive deposition of endometriotic tissue on the extracellular matrix (Matsuzaki and Darcha, 2014;Malutan et al, 2015) and may cause scar formation or alter tissue function (Matsuzaki et al, 2010). Wu et al (2018) reported that the increase in exosome miR-214 from endometrial stromal cells could result in the decrease of endometriosis fibrosis by reducing collagen αI and CTGF mRNA expression. Subsequently, Harp et al (2016) proposed that exosomes released by endometriotic stromal cells could deliver specific miRNA molecules in an autocrine and paracrine manner to promote the occurrence of endometriosis and regulate angiogenesis.…”
Section: Extracellular Vesicles and Endometriosismentioning
confidence: 99%
“…Daidzein-rich isoflavone aglycones, which is a dietary supplement, inhibits the proliferation of OESCs and reduces the expression of IL-6, IL-8, COX-2 and aromatase in OESCs (63). To study the association of miR-214 and fibrosis in endometriosis, the overexpression of miR-214 can be used, and in OESCs, significantly decreases the mRNA expression of αSMA, Col-I and CTGF (64). EEC16 cells are an ovarian endometriosis epithelial cell line that are isolated from superficial endometriosis lesions on the surface of the ovaries, which express a number of biomarkers at different levels when compared to normal ovarian epithelial cells, including the lack of N-Cadherin expression (14).…”
Section: Human Primary Endometrial Epithelial Cells (Eecs) and Endomementioning
confidence: 99%